DEVICE ADDICTION TO SOCIALIZATION STYLE - Sudirman Effary; Sukendar Sukendar; Supriyadi Supriyadi (Fox Justi : Jurnal Ilmu Hukum, 2021)
This research is motivated by the widespread use of gadgets in society. This study aims to describe how the influence of gadgets on social emotional development among adolescents to adults in Group 6 in Bandung, precisely in the Binong area. The research method used is descriptive qualitative research. This research approach uses the phenomenological method. The sample in this study amounted to 9 people. Based on the observations we have made in the area, the average use of gadgets in the area is quite high, of course with this we can get various and accurate information from informants in the area. the. The data collection technique used is interviews. There are several categories of informants, namely students (16-18 years), teenagers or students (19-25 years old) and finally there are parents (26-50 years). This shows that the use of gadgets has a positive effect of 30% and a negative effect of 70% on the development of addiction, social, emotional, adolescents and adults in group 6 in Bandung, precisely in the Binong area. However, the effect is not significant.